2017
DOI: 10.1016/j.tips.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Pot: Not Your Grandfather’s Marijuana

Abstract: In the early 2000’s in Europe and shortly thereafter in the USA, it was reported that “legal” forms of marijuana were being sold under the name K2 and/or Spice. Active ingredients in K2/Spice products were determined to be synthetic cannabinoids (SCBs), producing psychotropic actions via CB1 cannabinoid receptors, similar to those of Δ9-THC, the primary active constituent in marijuana. Often abused by adolescents and military personnel to elude detection in drug tests due to their lack of structural similarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 174 publications
(221 reference statements)
1
69
0
3
Order By: Relevance
“…As such, because non-biased, full agonists ( e.g. , JWH-018) at hCB 1 Rs produce tolerance and dependence following chronic administration (70), this study tested if PNR-4-20 would exhibit diminished levels of these adverse effects. In vivo studies revealed that chronic PNR-4-20 treatments result in less persistent tolerance to cannabinoid-induced hypothermia while producing no significant withdrawal behaviors when challenged with a CB 1 R antagonist.…”
Section: 0 Discussionmentioning
confidence: 99%
“…As such, because non-biased, full agonists ( e.g. , JWH-018) at hCB 1 Rs produce tolerance and dependence following chronic administration (70), this study tested if PNR-4-20 would exhibit diminished levels of these adverse effects. In vivo studies revealed that chronic PNR-4-20 treatments result in less persistent tolerance to cannabinoid-induced hypothermia while producing no significant withdrawal behaviors when challenged with a CB 1 R antagonist.…”
Section: 0 Discussionmentioning
confidence: 99%
“…As well as this change in cannabis itself, the preferred routes of administration and development of associated cannabis concentrates have increased the levels of potency that users are exposed to. [10] To further complicate matters, the role that synthetic cannabinoids play is not clear, with a growing body of evidence to suggest that not only is their use becoming more popular but also that there are significant toxic effects on brain and behavior. [11] It also seems that exogenous factors play a role in how effective cannabis might be as an antidepressant with its effects being greatest under aversive conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, highly variable and serious adverse clinical effects including altered mental status, cardiotoxicity, seizures, acute kidney injury, hyperthermia, and death have been reported [2]. While these effects have been well documented, the degree to which users are impaired in the context of motor vehicle operation has not been thoroughly addressed in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic cannabinoids are the most common NPS and are a structurally diverse class with over 250 specific cannabinoids reported to be available [1]. Illegal laboratories make simple modifications to one or more structural components to mimic the effects of Δ9-tetrahydrocannabinol (Δ-THC), evade laboratory detection, and challenge law enforcement, regulatory frameworks, and medical care providers [2]. These new designer drugs are commonly referred to as either “K2” or “Spice”.…”
Section: Introductionmentioning
confidence: 99%